Evaluation and driving factors of sustainable development of the wetland ecosystem in Northeast China: An emergy approach. (1st March 2020) - Song, Fei; Su, Fangli; Zhu, Dan; Li, Lifeng; Li, Haifu; Sun, Di
Abstract: The Northeast is one of the regions with the most extensive wetland area in China, which provides important environmental support for social development. However, agricultural reclamation and socio-economic development have changed the land use of wetland ecosystems, resulting in the continuous loss of natural wetland area and affecting the sustainable development of wetlands. In this study, an emergy accounting approach was used to evaluate the sustainable development status of the wetland ecosystem in Northeast China from 1980 to 2015. The results showed that the purchased resources (P) replaced the local renewable resources (R) and the local non-renewable resources (N) as the largest emergy flow after 2000. This change led to a negative development of the emergy indicators. The emergy yield ratio (EYR) decreased from 5.63 to 2.04, the environmental load ratio (ELR) increased from 1.90 to 3.58, and the emergy sustainability indicator (ESI) decreased from 2.96 to 0.57, indicating that the sustainable development of wetlands deteriorated during the study period. Next, the Logarithmic Mean Divisia Index decomposition analysis (LMDI) was applied to decompose the change of the ESI (ΔESI) into 5 driving factors. The results showed that the external pressure factor (Aw /P) had a decisive impact on sustainable development, and the other four factors indicated that renewable resources had a positive contribution to improving sustainable development. Therefore, this study proposes to improve sustainable development from three aspects: firstly, restore or expand the wetland area; secondly, reduce the input of purchased resources; and thirdly, increase the application of renewable resources. Such findings can provide valuable suggestions for the government to better manage wetlands. Highlights: Externally purchased resources became the most important part of the total emergy used in the study area. The three emergy indicators were negatively developed. The sustainability index of wetland fell from 2.96 to 0.57. The external pressure factor (Aw /P) had a decisive impact on the sustainable development of the wetlands. Renewable resources have a positive contribution to improving the sustainable development of the wetland.